Survival and differentiation effects of pigment epithelium derived factor (pedf) on retina neurons - Politi, Luis Enrique (2017)
PEDF promotes survival of photoreceptor cells and in an R28 retinal progenitor cell line by binding to PEDF membrane receptors. However, the intracellular molecular effects of PEDF in retina neurons are still unknown. Here we investigated these effects using pure neuronal cultures of photoreceptors and amacrine neurons, prepared from newborn rat retina and grown in a chemically defined medium. Cultures were supplemented at day 2 with either recombinant human PEDF (10 nM); PEDF plus P1 (a PEDF receptor blocking peptide, 100nM); or vehicle (control). At day 5, cells were fixed and cell death and apoptosis were evaluated by DAPI staining, Propidium Iodide and TUNEL assays, respectively. Mitochondrial activity was assessed with Mitotracker and opsin expression and axonal outgrowth were determined by immunocytochemical methods. PEDF decreased the percentages of Propidium Iodide and TUNEL-positive photoreceptors by 55% and 65%, respectively, with respect to controls without PEDF, and significantly prevented the loss of mitochondrial membrane potential. Pre-incubation with the blocking P1 peptide abolished PEDF effects. PEDF had no effect on opsin expression but promoted its apical localization in photoreceptors as occurs in mature retinas, in contrast to its diffuse distribution on the cell body in controls. PEDF also stimulated axon outgrowth in amacrine neurons, by 2-fold, in neurons treated with PEDF, compared to controls. These effects were blocked by the blocking P1 peptide pre-treatment. In summary, this work shows that PEDF acts as a survival factor for photoreceptors, preserving their mitochondrial functionality, and induces the differentiation of amacrine and photoreceptor neurons during their development in vitro.